2015
DOI: 10.1007/s10508-015-0525-1
|View full text |Cite
|
Sign up to set email alerts
|

Sociocognitive Predictors of Condom Use and Intentions Among Adolescents in Three Sub-Saharan Sites

Abstract: Many HIV intervention programs in sub-Saharan Africa have applied social cognitive theories such as the theory of planned behavior. However, a recent sub-Saharan African review was unable to show increased effectiveness for theory-based interventions. This study assessed whether the predictive value of attitudes, subjective norms, self-efficacy, and intention was similar to studies in Europe and the U.S., and whether there were differences between three sub-Saharan sites. Longitudinal multigroup structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
41
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 71 publications
12
41
0
5
Order By: Relevance
“…A study in three sub‐Saharan countries found that more prevalent traditional gender roles including “the male is supposed to take the initiative and responsibility for safe sex practices such as condom buying and negotiating”, inhibit safe sex practices (Eggers et al . ). Our study found no significant correlation between behavioural intention to use condoms at every sexual encounter, self‐efficacy to use condoms, and the norm for sexual relationships/habits among girls and boys.…”
Section: Discussionmentioning
confidence: 97%
“…A study in three sub‐Saharan countries found that more prevalent traditional gender roles including “the male is supposed to take the initiative and responsibility for safe sex practices such as condom buying and negotiating”, inhibit safe sex practices (Eggers et al . ). Our study found no significant correlation between behavioural intention to use condoms at every sexual encounter, self‐efficacy to use condoms, and the norm for sexual relationships/habits among girls and boys.…”
Section: Discussionmentioning
confidence: 97%
“…Most notably we found that the proximal TPB constructs of subjective norms and perceived behavioural control explained a total of 46% of the variance in the intention to use a condom consistently with every sexual encounter. This finding is comparable to other studies (Boer & Mashamba, 2007;Eggers et al, 2016;Fazekas, Senn, & Ledgerwood, 2001;Giles et al, 2005) in African countries, which have also shown subjective norms to be a stronger cognition predictor of intention to use condoms when it is compared to other proximal cognition constructs, namely attitudes and perceived behavioural control. The total variance in intention to use condoms explained in these other studies ranges between 22% and 67%, however it has been recently reported that in general the predictive value for TPB constructs in sub-Saharan Africa is on average less than that of North American and European studies (Eggers et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…In South Africa, more specifically, a few studies have used the Theory of Planned Behaviour as a framework to research gender power imbalances in the intention to use condoms (Boer & Mashamba, 2007), the role of individual and group factors in intentions to use condoms (Giles, Liddell, & Bydawell, 2005), adolescent condom use behaviour (Bryan, Kagee, & Broaddus, 2006;Eggers et al, 2016;, the influence intention has on behaviour among university students (Heeren et al, 2007), and condom use motivation in traditional male circumcision initiates (Nyembezi et al, 2014). These studies also vary in their prediction of the | 69 most influential cognitive constructs, and some also show a clear gender difference in their predictability where both sexes were sampled.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses the socio-cognitive factors of behavioral intention, attitude, subjective norm, and perceived behavioral control/ self-efficacy to assess associations with actual sexual behavior. The study also includes other factors such as knowledge and psychological barriers that have been widely used and studied in sub-Saharan Africa (SSA) as predictors of behavior (Obare et al, 2011;Bakibinga et al, 2016;Eggers et al, 2016;Krugu, Mevissen, Debpuur, & Ruiter, 2016). The outcome measure are the actual sexual behaviors (condom use, multiple sexual partnerships, and contraception use) among sexually active adolescent girls.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 99%